2010
DOI: 10.1007/s00247-010-1848-7
|View full text |Cite
|
Sign up to set email alerts
|

The positive color Doppler sign post biopsy: effectiveness of US-directed compression in achieving hemostasis

Abstract: Color Doppler US can detect bleeding post percutaneous liver and kidney biopsies. US-guided compression is effective in obliterating the color Doppler signal and achieving appropriate hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Color Doppler US (CDUS) is a sensitive modality for detecting hemorrhage in various organs. Some reports have shown the usefulness of CDUS for detecting post-liver biopsy hemorrhaging (10)(11)(12). CDUS demonstrates a linear color flow signal along the needle tract immediately after a biopsy and is useful for screening for postbiopsy hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Color Doppler US (CDUS) is a sensitive modality for detecting hemorrhage in various organs. Some reports have shown the usefulness of CDUS for detecting post-liver biopsy hemorrhaging (10)(11)(12). CDUS demonstrates a linear color flow signal along the needle tract immediately after a biopsy and is useful for screening for postbiopsy hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…The technique has been described previously in biopsy procedures of children and of the prostate. 13,14 This color sign is real blood flow and not artifactual. 14 The duration of bleeding can be reduced by graded compression with the probe at least until no bleeding is observed without compression.…”
Section: Discussionmentioning
confidence: 94%
“…Color Doppler ultrasound (CDUS)-guided compression of the soft tissue biopsy needle tract in the case of bleeding has previously been described in pediatric and prostate biopsy procedures. 13,14 The aim of this study was to describe the technique of using CDUS guidance in planning, acquisition, and, in the case of bleeding, compression of the needle tract. The frequency of observed needle tract bleeding in biopsy procedures of kidney transplants is reported.…”
mentioning
confidence: 99%
“…In fact, morbidity and mortality rates are not high. Furthermore, regarding bleeding after PLB, Alotaibi et al [4] described that the positive color Doppler sign in US indicated bleeding along a biopsy tract and US-guided compression was effective in achieving appropriate hemostasis, and tract-plugging means that the biopsy tract is filled with Gelfoam or other thrombotic agents, it is an important procedure to decrease the risk of bleeding and subcapusular hematoma in PLB [2]. Nevertheless, in patients with ascites, abnormal coagulation profiles, another procedure is considered because of the high risk due to bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are two minimally invasive techniques for liver tissue sampling: imageguided percutaneous liver biopsy (PLB) and transjugular liver biopsy (TJLB) [1][2][3][4]. Both techniques have several disadvantages, such as the risk of bleeding and subcapsular hematoma in the former, and the small sample size, longer procedure time and the need for considerable interventional skill in the latter.…”
Section: Introductionmentioning
confidence: 99%